2021
DOI: 10.1080/19768354.2021.1943707
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 3 contributes to tumorigenicity of pancreatic ductal adenocarcinoma through activating Src–FAK signaling

Abstract: Desmogleins (DSGs), with the ability to link adjacent cells, have been shown to participate in the development of malignancy. DSG3 was up-regulated in various cancers, including lung, head and neck, and esophagus squamous cell carcinoma, which contributed to the tumor progression. The role of DSG3 in pancreatic ductal adenocarcinoma (PDAC) still remains elusive. Here, the expression of DSG3 was found to be enhanced in pancreatic cancer cell lines in vitro. Functional assays showed that shRNA-mediated knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Notably, DSG3 emerged as another classifier among the analyzed molecules. These findings align with previous functional studies highlighting the significant role of DSG3 in tumor progression, particularly in differentiating adenocarcinoma (ADC) from squamous cell carcinoma (SCC) [48,49].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, DSG3 emerged as another classifier among the analyzed molecules. These findings align with previous functional studies highlighting the significant role of DSG3 in tumor progression, particularly in differentiating adenocarcinoma (ADC) from squamous cell carcinoma (SCC) [48,49].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, overexpression of LAMC2 promoted the expression of proteins related to integrin β 1/FAK/Src/AKT molecules, and knockdown of LAMC2 inhibited the expression of proteins related to integrin β 1/FAK/Src/AKT molecules, which further proved that LAMC2 promoted cell proliferation and invasion through the integrin β 1/FAK/Src/AKT signaling pathway. This was similar to what Abula et al found in PDAC cells, where PDAC proliferation and invasion were promoted by activating the Src/FAK/AKT signaling pathway [ 44 ]. Furthermore, Guo et al found that Src/Fak, Akt, and Erk1/2 signaling regulate proliferation and migration of gastric cancer cells [ 45 ].…”
Section: Discussionsupporting
confidence: 89%
“…AREG, a recently discovered molecule, mediates EMT of PC via the EGFR/ERK/NF-κB signaling pathway, which promotes PC growth and metastasis 44 . DSG3 is involved in numerous cell biology functions (cell growth and differentiation) 45 , is considered a negative prognostic biomarker for resected PC 46 and promotes PC tumorigenicity through the activation of the Src-FAK signaling pathway 47 . This study found that DSG3 was associated with higher clinical staging in PDAC patients and that its high expression predicted a worse outcome in PDAC patients.…”
Section: Discussionmentioning
confidence: 99%